Efektivitas Pemberian Makanan Tambahan Terhadap Lingkar Lengan Atas pada Ibu Hamil Kekurangan Energi Kronik (KEK) di Kabupaten Sleman - Lidwina Pandhita Febriyani; Dittasari Putriana; Ibtidau Niamilah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Chronic Energy Deficiency (CED) in pregnant women remains a health problem in Indonesia, including in Sleman District. CED can be overcome through the provision of supplementary foods (PMT) based on local foods that are high in energy and protein. This study aims to determine the effectiveness of local PMT on upper arm circumference (UAC) in pregnant women with CED. The study design used an analytical observational approach with a cross-sectional approach. The sampling technique used in this study was total sampling, involving 47 pregnant women with CEM who received local PMT for at least 90 days in 2024 at the Cangkringan and Sleman Community Health Centers. The secondary data in this study were the results of LILA measurements before and after the provision of local PMT. The Wilcoxon Signed Test was used to analyze the difference in LILA. The results showed that the median LILA before PMT administration was 22 cm and after PMT administration was 23.6 cm, with an increase of 1.6 cm. There was a significant difference between LILA before and after local PMT administration (p = 0.000). After local PMT administration, 51.06% of pregnant women had LILA > 23.5 cm. It is hoped that further research can explore the intake of pregnant women with KEK during local PMT administration as additional data to examine the effectiveness of local PMT on LILA in pregnant women with KEK.